2008
DOI: 10.1371/journal.ppat.0040006
|View full text |Cite
|
Sign up to set email alerts
|

Distinct TLR- and NLR-Mediated Transcriptional Responses to an Intracellular Pathogen

Abstract: How the innate immune system tailors specific responses to diverse microbial infections is not well understood. Cells use a limited number of host receptors and signaling pathways to both discriminate among extracellular and intracellular microbes, and also to generate responses commensurate to each threat. Here, we have addressed these questions by using DNA microarrays to monitor the macrophage transcriptional response to the intracellular bacterial pathogen Listeria monocytogenes. By utilizing combinations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
235
3
2

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 196 publications
(253 citation statements)
references
References 60 publications
(76 reference statements)
13
235
3
2
Order By: Relevance
“…Following phagocytosis and escape into the cytosol, it is sensed by NLRs, namely the Nod1, Ipaf, and Nalp3 inflammasomes (14,15). The concerted actions of these pathways translate into a robust sterilizing immunity and enhanced pathogen elimination (16).…”
mentioning
confidence: 99%
“…Following phagocytosis and escape into the cytosol, it is sensed by NLRs, namely the Nod1, Ipaf, and Nalp3 inflammasomes (14,15). The concerted actions of these pathways translate into a robust sterilizing immunity and enhanced pathogen elimination (16).…”
mentioning
confidence: 99%
“…This has been demonstrated for Listeria monocytogenes as well as Shigella flexneri and L. pneumophila (39,40,58,59). The induction of IFN-b in Listeria-, Legionella-, or group B streptococci-infected macrophages was supposed to be mediated by the DNA-recognition pathway (35,37,40). The observation that the type IV secretion apparatus is required to initiate the type I IFN response in L. pneumophila and Brucella (39,40,60) suggests that the functionally analogous but evolutionary unrelated type III secretion apparatus of C. pneumoniae may be a crucial element in the IFN-b response.…”
Section: Discussionmentioning
confidence: 92%
“…However, the PRR(s) as well as the signaling pathway(s) activated in bacteria-infected host cells, which mediate IFN-b production remain incompletely understood. It has been suggested that DNA from intracellular bacteria or from bacteria that were engulfed by phagocytic cells is recognized by poorly characterized cytosolic PRRs (35)(36)(37)(38)(39)(40). Downstream of these PRRs, the Tankbinding kinase-1 and IRF3 are involved in the bacteria-stimulated IFN-b pathway (40)(41)(42)(43).…”
mentioning
confidence: 99%
“…In these experiments, both wild-type and MyD88 2/2 DCs were equally capable of inducing DN32 cells to elevate CD69 and IL-2 expression. In addition to components activating TLR pathways, reports have described the peptidoglycan constituent muramyl dipeptide (MDP), recognized by the intracellular NOD2 receptor, as one of the major adjuvant activities of M. tuberculosis (50,51). As a consequence, we investigated whether MDP can activate NKT cells by incubating DN32 cells with treated BMDCs in vitro.…”
Section: /2mentioning
confidence: 99%